Miles Morales. Shock waves : a Spider-Man graphic novel - Reynolds, Justin A. (Graphix, 2021)
Miles Morales--the Spider-Man of Brooklyn--sets up a fundraiser to help the devastated island of Puerto Rico, his mother's homeland, after an earthquake. However, when a new student's father disappears and it comes to light that he had connections to the corporation helping Miles' fundraiser, it seems Spider-Man has a new job.